FAKTOR PENYEBAB YANG BERHUBUNGAN DENGAN PEMBERIAN MP-ASI PADA BAYI USIA 0-6 BULAN DI UPTD PUSKESMAS KEMALARAJA KABUPATEN OKU - Oktarida, Yustina (Fakultas Ilmu Kesehatan Universitas Katolik Musi Charitas, 2019)
Giving weaning food too early has a very high risk of contamination, which is the occurrence of gastroenteritis which is very dangerous for the baby and can reduce milk production because babies rarely breastfeed. The purpose of this study was to find out the factors related to the administration of MP-ASI in infants aged 0-6 months in the UPTD of Kemalaraja Health Center in 2017. The quantitative research design was an analytical survey with a cross sectional approach. The population in this study were all mothers who had babies aged 0-6 months who came to the UPTD of Kemalaraja Health Center in January - March 2017, samplingconducted by accidental sampling with a total sample of 50 people and the measuring instrument used was a questionnaire. Data analysis included univariate and bivariate using the chi-square test. The results of statistical tests found that there is a relationship between maternal education (pvalue = 0.004), family income (p-value = 0.001) support family (p-value = 0.003) by giving weaning food to infants aged 0-6 months at the UPTD in Kemalaraja Health Center in 2017.   Keywords: Weaning Food, Education, Family Income, Family Support